Embarazo adolescente como factor de riesgo para complicaciones obstétricas y perinatales en un hospital de Lima, Perú - Okumura, Javier A. (2015)
Objective: to evaluate the risk of obstetric and perinatal outcomes in teenage pregnancy in comparison with adult pregnancy. Methods: retrospective cohort study of 67.693 pregnant women attended in a public hospital in Lima between 2000 and 2010. Obstetric and perinatal outcomes were evaluated. The adolescent group was divided in late adolescents (15-20 years), and early adolescents (<15 years) and was compared among the adult group (20-35 years). Adjusted odds ratios were calculated by education, civil status, prenatal care, previous pregnancies, parity, and pre-gesta-tional BMI. Results: higher risk of cesarean (OR=1,28; CI95%=1,07-1,53) and puerperal infection (OR=1,72; CI95%=1,17-2,53) was found in teenager under 15 years old; as well as higher risk of episiotomy (OR=1,34; CI95%=1,29-1,40) in late teenagers. In addition, this study identified a lower risk of teenage pregnancy for preeclampsia (OR=0,90; CI95%=0,85-0,97), 2nd half-pregnancy bleeding (OR=0,80; CI95%=0,71-0,92), premature rupture of membranes(OR=0,83; CI95%=0,79-0,87), preterm labor (OR=0,87; CI95%=0,80-0,94) and vaginal tearing (OR=0,86; CI95%=0,79-0,93). Conclusion: pregnancy behaves as a risk factor for some obstetric outcomes in the adolescent group, especially in the youngest ones. In addition to maternal age, there are other factors that constitute the need to form multidisciplinary teams to reduce obstetric outcomes in this population.